2014
DOI: 10.1007/978-3-319-04981-6_7
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular Events After Subarachnoid Hemorrhage: Focusing on Subcellular Organelles

Abstract: Subarachnoid hemorrhage (SAH) is a devastating condition with high morbidity and mortality rates due to the lack of effective therapy. Early brain injury (EBI) and cerebral vasospasm (CVS) are the two most important pathophysiological mechanisms for brain injury and poor outcomes for patients with SAH. CVS has traditionally been considered the sole cause of delayed ischemic neurological deficits after SAH. However, the failure of antivasospastic therapy in patients with SAH supported changing the research targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 77 publications
(77 reference statements)
0
24
0
Order By: Relevance
“…Nevertheless, our findings may be consistent with the recent idea of early brain injury as the key pathologic mechanism in SAH 13 . This phenomenon begins immediately after cerebral hemorrhage, and is known to trigger cell death along with mitochondrial dysfunction 14 . Our CSF mitochondrial membrane potential measurements at day 1 after SAH showed significant reduction compared to controls, and recovery in these values at day 3 appear to correspond with patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our findings may be consistent with the recent idea of early brain injury as the key pathologic mechanism in SAH 13 . This phenomenon begins immediately after cerebral hemorrhage, and is known to trigger cell death along with mitochondrial dysfunction 14 . Our CSF mitochondrial membrane potential measurements at day 1 after SAH showed significant reduction compared to controls, and recovery in these values at day 3 appear to correspond with patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…During EBI, subcellular organelle functions become disordered, and the autophagy-lysosomal system is activated (Chen et al, 2015 ). As the main intracellular recycling system during conditions of starvation and various stressors, autophagy is a critical for neuronal survival (Mizushima and Komatsu, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods can only reduce a part of occurrence of CVS [22]. Our previous studies have showed that specific knocking down Cx43 in spastic cerebral arteries with specific siRNA interference can significantly alleviate CVS after SAH.…”
Section: Discussionmentioning
confidence: 99%